2016
DOI: 10.1159/000446016
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Sustained Intraocular Pressure Elevation after Multiple Intravitreal Injection of Ranibizumab and Aflibercept for Neovascular Age-Related Macular Degeneration

Abstract: Intravitreal injections of anti-vascular endothelial growth factor (VEGF) agents are widely used to treat neovascular age-related macular degeneration (nAMD). Although these treatments are effective, multiple injections have recently been recommended to ensure that there is a good long-term prognosis. However, sustained intraocular pressure (IOP) elevations have been reported to develop after multiple injections of anti-VEGF agents. We present our findings of a case of uncontrolled and persistent IOP elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Intravitreal injection of anti-VEGF drugs can lead to an increased long-term IOP. 4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] Several mechanisms to explain this phenomenon including the possibility that protein aggregates and silicone oil microdroplets are responsible for the IOP elevation are discussed. [22][23][24] Protein aggregates can be formed Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravitreal injection of anti-VEGF drugs can lead to an increased long-term IOP. 4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] Several mechanisms to explain this phenomenon including the possibility that protein aggregates and silicone oil microdroplets are responsible for the IOP elevation are discussed. [22][23][24] Protein aggregates can be formed Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies with different number of patients followed reporting prevalence of long-term IOP rise after treatment with ranibizumab, bevacizumab, or aflibercept injections. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recent retrospective analysis of the VIEW 1 and 2 data of 2,457 patients showed significant higher IOP elevation in ranibizumab than in aflibercept injected eyes. 21 This study showed for the first time in a high number of patients a statistically significant IOP elevation difference between these two agents.…”
mentioning
confidence: 99%
“…A meta-analysis of 46 articles by De Varies et al reported a mean rise of 23.4 mmHg returning to baseline after one week [20]. On the contrary, multiple other studies have shown IOP returning to safer levels within half an hour after the injection without any intervention [21,22]. These varying results can be because of the different types of patient cohorts used in the studies.…”
Section: Discussionmentioning
confidence: 98%
“…17 Over the years, several other studies have been published with varying numbers of patients reporting the prevalence of longterm IOP increase after treatment with bevacizumab, ranibizumab or aflibercept injections. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] One of the studies with the largest number of patients (retrospective analysis of VIEW 1 and 2 study data from a total of 2457 patients) showed a significantly higher IOP increase in eyes after ranibizumab treatment than in patients after aflibercept treatment. 31 In 2016 Zhou et al conducted a meta-analysis of 5 randomized controlled trials (RCT) in 1428 patients and 8358 patients from 17 non-RCTs.…”
Section: Possible Side Effects From Intravitreal Injections Elevated mentioning
confidence: 99%